Antioxidant and In Vitro Antidiabetic Properties of Lansium domesticum Leaves Extracted with Solvents of Varying Polarity - Situmorang, Jiro Hasegawa; Yulyana, Ana; Astyka, Ririn; Syahputra, Hafid; Lubis, Muhammad Fauzan (Indonesian Journal of Chemistry, 2026)
Conventional therapies for diabetes mellitus, such as oral hypoglycemic agents, are often limited by side effects and incomplete glycemic control, highlighting the need for safer alternatives. Exploring natural remedies, such as Lansium domesticum, is compelling, as this plant has been traditionally used for diabetes therapy. This study aimed to investigate how solvent polarity and affinity influence phytochemical content, antioxidant activity, and enzyme inhibitory potential of L. domesticum leaf extracts. Extraction was conducted using methanol, ethanol, and acetone (50%, 75%, 100%), and distilled water. Total phenolic content (TPC) and total flavonoid content (TFC) were quantified, and antioxidant activities were assessed via total antioxidant activity (TAA), DPPH, and FRAP assays. Antidiabetic activity was evaluated in vitro through α-glucosidase and α-amylase inhibition assays. The results indicated that 100% ethanol extract exhibited the highest TPC and TFC, correlating strongly with superior antioxidant and enzyme inhibitory activities. The extract has also demonstrated the most potent inhibition of α-glucosidase and α-amylase, with IC50 values of 70.64 and 105.13 µg/mL, respectively. Pearson correlation analysis revealed strong negative correlations between phytochemical contents and IC50 values. Overall, ethanol proved to be the most effective solvent for extracting bioactive compounds from L. domesticum leaves, underscoring its potential as a natural antioxidant and antidiabetic agent.